2019
DOI: 10.1089/dia.2019.0064
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of an Automated Bolus Calculator in Pediatric Patients with Type 1 Diabetes on Multiple Daily Injections: The Expert Kids Study

Abstract: Background: This multicenter crossover study investigated the potential beneficial effect of an automated bolus calculator (ABC) in children and adolescents with type 1 diabetes (T1D) treated with multiple daily injections (MDI). Methods: Participants were randomized to either begin or end with a 5 months intervention versus their regular treatment regimen (control), separated by a 2 months washout period. During the intervention participants were carefully instructed to use the ABC (Accu-Check Aviva Expert) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In the past, it has been suggested that bolus calculator use could improve outcomes when used consistently by people with T1D, 14 , 15 but a recent well-designed 10-month randomized crossover study using an automated bolus calculator device failed to show improvements in HbA1c or quality of life. 16 Although this study was conducted using a simpler bolus calculator based on static BG readings for multiple daily injection users, the requirement for the user to enter insulin doses and BG readings manually for correct usage likely affected outcomes. When designing new diabetes technology or treatment methods, it is important to consider the ease of use and burden placed on the user for correct use, which will influence the success of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, it has been suggested that bolus calculator use could improve outcomes when used consistently by people with T1D, 14 , 15 but a recent well-designed 10-month randomized crossover study using an automated bolus calculator device failed to show improvements in HbA1c or quality of life. 16 Although this study was conducted using a simpler bolus calculator based on static BG readings for multiple daily injection users, the requirement for the user to enter insulin doses and BG readings manually for correct usage likely affected outcomes. When designing new diabetes technology or treatment methods, it is important to consider the ease of use and burden placed on the user for correct use, which will influence the success of the treatment.…”
Section: Discussionmentioning
confidence: 99%